2014
DOI: 10.1155/2014/983098
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Combining Galectin-3 and BIVA Assessments in Predicting Short- and Long-Term Events in Patients Admitted for Acute Heart Failure

Abstract: Introduction. Acute heart failure (AHF) is associated with a higher risk for the occurrence of rehospitalization and death. Galectin-3 (GAL3) is elevated in AHF patients and is an indicator in predicting short-term mortality. The total body water using bioimpedance vector analysis (BIVA) is able to identify mortality within AHF patients. The aim of this study was to evaluate the short- and long-term predictive value of GAL3, BIVA, and the combination of both in AHF patients in Emergency Department (ED). Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…In detecting congestion and latent fluid overload, BIVA has greater diagnostic sensitivity than other techniques (including fluid balance), and it also shows an emerging role for its prognostic value [16]. Previous data from our group demonstrates that the reduction of congestion detected by BIVA, during AHF patients hospitalization, is linked with an improvement in patients' outcome [17,20,23].…”
Section: Discussionmentioning
confidence: 85%
“…In detecting congestion and latent fluid overload, BIVA has greater diagnostic sensitivity than other techniques (including fluid balance), and it also shows an emerging role for its prognostic value [16]. Previous data from our group demonstrates that the reduction of congestion detected by BIVA, during AHF patients hospitalization, is linked with an improvement in patients' outcome [17,20,23].…”
Section: Discussionmentioning
confidence: 85%
“…Moreover, Gal-3 changes in patients were shown to be a strong prognostic indicator [ 29 ]. In addition, Gal-3 levels have a potential role in early detection of myocardial structural and functional alterations [ 30 ] and risk stratification in HF [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the 64-detector computed tomography could provide a good diagnostic performance in congenital heart disease [ 31 ], which depends on the understanding of normal fetal cardiac anatomic structure; meanwhile, some new studies demonstrated that the identification and characterization of the cellular and molecular pathways involved in the differentiation and morphogenesis of specific cell types of the developing heart were crucial to understanding the process of cardiac development and the pathology associated with human congenital heart disease, and they found that the CHD5 (congenital heart disease 5 protein) was essential for CASZ1 (cardiac transcription factor CASTOR) function and that the CHD5-CASZ1 interaction was necessary for cardiac morphogenesis and numerous signaling pathways were critical for normal valve development which could be reexpressed in diseased valves [ 32 – 35 ]. The increased level of PTX3 is also an independent predictor of combined end point of left ventricle dysfunction or mortality at one year; combining the biomarker and the device could be of great utility since they monitor the severity of two pathophysiological different mechanisms: heart fibrosis and fluid overload [ 36 ]. However, the data of fetal heart gross anatomy is rare.…”
Section: Discussionmentioning
confidence: 99%